Korelasi antara Konsumsi Makanan Pedas dan Asam dengan Gejala Asam Lambung pada Mahasiswa Universitas Muhammadiyah Bandung - Nisa Ihsani; Desti Raflianti; Mahesa Dhiyaa Alkhairan; Nadila Suci Nugraha; Wafa (Jurnal Biodiversitas dan Bioteknologi, 2024)
Nowadays, spicy and sour foods are very popular among teenagers, especially among college students. Snacks with spicy and sour flavors are enjoyed by various age groups because some of them offer the distinctive taste of West Java, particularly from the city of Bandung. Excessive consumption of spicy food can lead to health issues, as spicy foods contain capsaicin, which can stimulate pain receptors in the digestive tract. This observational study was carried out by distributing questionnaires containing a set of written questions to gather research data from 176 students at Universitas Muhammadiyah Bandung. This study sought to identify the proportion of preferences for spicy and sour foods. It also examined the relationship between the preference for spicy food and the occurrence of acid reflux symptoms. This research also analyzed the connection between the preference of spicy food and the symptoms of acid reflux. The results showed that a total of 79% of respondents liked spicy food, while the remaining (21%) were not into spicy and sour food (p<0.05). However, the preference for spicy food did not correlate with the occurrence of the acid reflux of the respondents (p>0.05). Meanwhile, 48% of respondents like sour food, while 52% do not like it (p>0.05).